To what extent will women accept HPV self-sampling for cervical cancer screening? A qualitative study conducted in Switzerland - Fargnoli V; Petignat P; Burton-Jeangros C (Dove Medical Press, 2015)
Vanessa Fargnoli,1 Patrick Petignat,2 Claudine Burton-Jeangros1 1Department of Sociology, University of Geneva, Geneva, Switzerland; 2Department of Gynecology and Obstetrics, Geneva University Hospitals, Geneva, Switzerland Objectives: Human papillomavirus self-sampling (self-HPV) is regarded as an alternative to Pap smear testing for women who do not participate in cervical cancer screening. This qualitative study aimed to determine women’s views on cervical cancer screening and the various obstacles to participation in screening, and to evaluate the perceived benefits and disadvantages of self-HPV. Method: Twenty-four focus groups were conducted in 2012, with a total of 125 participants aged between 24 and 67 years. They were recruited through different channels, including flyers and posters, personal contacts, and an ongoing clinical trial focused on the unscreened population. Interview transcripts have been coded with the ATLAS.ti CAQDAS. Results: Fifty-seven participants regularly attended screening and 68 had not been screened in the past 3 years. While some participants considered self-HPV as an acceptable screening method, others expressed concerns. Benefits included access, reduced costs, and time-saving. Disadvantages included the fear of not performing the test correctly, hurting oneself, and the accuracy of the test. Participants expressed concern that self-HPV would replace gynecological visits. Conclusion: Self-HPV is not likely to rapidly or substantially modify women’s behaviors in regard to screening. While it may offer benefits in some specific situations, most women emphasized the advantages of regular gynecologist visits. Keywords: self-HPV, cervical cancer, cervical screening, qualitative study, Pap smear